Efficacy of enteral ticagrelor in hypothermic patients after out-of-hospital cardiac arrest - Tilemann, Lisa; Stiepak, Jan; Zelniker, Thomas; Chorianopoulos, Emmanuel; Giannitsis, Evangelos; Katus, Hugo; Müller, Oliver J.; Preusch, Michael (Clinical research in cardiology, 2016)
IntroductionDelivery of crushed ticagrelor via a nasogastric tube is a widely spread off-label use in unconscious patients following out-of-hospital cardiac arrest (OHCA). Notwithstanding the importance of a potent dual antiplatelet therapy in these patients, the efficacy of crushed ticagrelor after OHCA has not been established yet.MethodsIn a prospective, single-center, observational trial, 38 consecutive MI patients after OHCA were included. 27 patients (71.1 %) underwent mild induced hypothermia. The primary outcome was platelet inhibition at 24h measured by impedance aggregometry.ResultsThere was sufficient platelet inhibition in most patients after OHCA. In all hypothermic patients, there was an adequate platelet inhibition by ticagrelor at 24 h (p < 0.001). 15 patients (39.5 %) had significant gastroesophageal reflux and one patient with significant reflux had inadequate platelet inhibition at 24 h. There were no stent thrombosis or recurrent atherothrombotic events in these patients.ConclusionAdministration of crushed ticagrelor via a nasogastric tube reliably inhibited platelet function in vitro and in vivo regardless of the presence of hypothermia in MI patients. Thus, platelet inhibition can be reliably achieved in MI patients during neuroprotective hypothermia following OHCA.
Published online: 27 October 2015
Gesehen am 17.12.2019